Frequency inborn error of mitochondrial function in Mosul and Kurdistan region - Ashwaq N. Abbas; Mwafak K. Hasan; Muhammad A. Ahmed (College of Pharmacy University of Baghdad, 2020)
This work aimed to estimate the frequency of mitochondrial inborn errors of metabolism (MIEMs) in patients presenting with family history and IEM-picture who referred for advance IEM assay in Mosul province and Kurdistan region. This study was observational study conducted on 364 cases referred from different general /or private pediatric clinics with unexplained sign and symptoms and suspension of mitochondrial dysfunction. The study included 364 children with an age ranging from 1 month to 1 year. Started from January 2018 to January 2020. All patients referred with their full history review, notes about their clinical examination, and laboratory investigations including blood ammonia, serum lactate/ pyruvate, arterial blood gases. In addition to the standard laboratory-tests (kidney and liver functions, blood glucose, and complete blood picture) carried out in Sorain private Laboratory. The results of this work show that sixteen (4.4%) of cases were positive in the IEM screening test